Genetic variation, Phylogenetics and fruit quality characteristics of Physalis minima L. in Peninsular Malaysia - Norhanizan Usaizan (Tanjong Malim, 2017)
Genetic variation, Phylogenetics and fruit quality characteristics of Physalis minima L. in Peninsular Malaysia by Norhanizan Usaizan